Non Contact Temperature Monitoring System to Optimize Health Working Environment Based on IoT - Ardiantoro, Luki Ardi; Muslimin, Moh; Rosita, Yesy Diah (Journal of Intelligent Computing & Health Informatics, 2023)
During the ongoing COVID-19 pandemic, monitoring body temperature is a crucial concern for the community, and it serves as an essential step in understanding the health condition of an individual's body. The workers in environments that involve physical contact and are prone to dirt are at a higher risk of contracting COVID-19. In this study, we created a body temperature detector to optimize the working environment in the waste processing area of Mojokerto Regency. Several modules and devices have been utilized, including the Arduino Uno R3 module, an ultrasonic sensor for object detection and temperature sensing, MLX90614 for detecting body temperature, and a buzzer system. The SDLC (Build & Fix design) method was employed to simulate the actual conditions at the Randegan Landfill in Mojokerto. Consequently, the designed IoT device can automatically send information and provide follow-up through a network of various functions. It can be concluded that the developed body temperature detection device has the potential to minimize the risk of contracting COVID-19 and enhance healthier and more productive working conditions.